(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Susceptibility of three predatory arthropods namely Asian lady beetle, Harmonia axyridis (Pallas), lynx spider, Lycosa pseudoannulata (Boescriberg and Strand), and wolf spider, Oxyopes javanus (Thorell) to four commonly used biorational molecules viz. buprofezin, spinosad, emamectin benzoate and abamectin were determined in a brinjal ecosystem. Biorational pesticides were applied singly and in some selected combinations and their toxicity on the predators was recorded up to three sprayings in a confined habitat. Buprofezin caused no significant mortality of predators (2.87%, 0.32%, 0.96% mean mortality per spray of Asian lady beetle, lynx spider, and wolf spider respectively) and was found most compatible among the biorational molecules. However, other three tested molecules were found highly toxic for all predatory natural enemies when applied singly or in combination with buprofezin. Spinosad was most toxic for Asian lady beetles (21.84% mean mortality per spray) and lynx spiders (15.32 % mean mortality per spray) whereas abamectin (17.78% mean mortality per spray) for wolf spiders. It was observed that the number of spraying was very crucial and had a proportionate relationship with the mortality percentage of predators. Based on this study it is suggested that buprofezin could be considered to incorporate safely in the IPM program for brinjal pest management. J. Bangladesh Agril. Univ. 15(2): 234-238, December 2017